Successful management of a mediastinum abscess with sternum destruction caused by MSSA bloodstream infection - Hironobu Wada; Yuki Shina; Toshiko Kamata; Fumihiro Ishibashi; Hajime Tamura; Masahiro Toriumi; Kyoichi Matsuzaki; Shigetoshi Yoshida (Surgical Case Reports)
Abstract Background Multiple deep organ abscesses associated with Staphylococcus aureus bloodstream infection (SAB) have a high mortality rate, requiring rapid removal or drainage of infective foci with long-term appropriate antimicrobial therapy. Cases in which infective foci cannot be completely removed are challenging for their management. Case presentation A 77-year-old man developed multiple deep organ abscesses associated with SAB. The left anterior chest subcutaneous abscess continued into the right anterior mediastinum and had extensively destroyed the sternum. Necrotizing fasciitis was observed in the bilateral feet. The anterior mediastinum abscess was drained percutaneously, and the chest wall abscess was incised cautiously without causing an external pneumothorax. On the next day, right-sided pyothorax had developed, requiring pleural drainage. On the third day, debridement of anterior chest wall abscess followed by concurrent thoracoscopic pleural curettage and debridement of bilateral feet were performed. Thorough sternal debridement was not performed, considering the risk of respiratory failure due to the sternal defects. On the 24th day, sternum debridement and incisional drainage of sciatic rectus fossa abscess, which had been present since the time of admission, were performed to control persistent infection. The caudal half of the sternal body was resected, leaving the costal cartilage attachments. The general condition further improved without postoperative respiratory failure after the second surgery, leading to a transfer to the general ward on the 43rd day. Conclusions We successfully treated the severe multiple deep organ abscesses, including a mediastinum abscess with sternum destruction, by repeated removal of the infective foci while avoiding respiratory failure due to excessive debridement of the anterior chest wall, including the sternum.